The Beneficial Effects of Ferulic Acid Supplementation during In Vitro Maturation of Porcine Oocytes on Their Parthenogenetic Development - Kyung-Mi Lee; Sang-Hwan Hyun (The Korean Society of Animal Reproduction and Biotechnology, 2017)
Ferulic Acid (FA) is a metabolite of phenylalanine and tyrosine, a phenolic compound commonly found in fruits and vegetables. Several studies have shown that FA has various functions such as antioxidant effect, prevention of cell damage from irradiation, protection from cell damage caused by oxygen deficiency, anti-inflammatory action, anti-aging action, liver protective effect and anti-cancer action. In this study, we investigated the maturation rate, intracellular glutathione (GSH) and reactive oxygen species (ROS) of porcine oocytes by adding FA to the in Vitro maturation (IVM) medium and examined subsequent embryonic developmental competence at 5% oxygen through parthenogenesis. There is no significant difference between the control group (0μM) and treatment groups (5μM, 10μM, 20μM) on maturation rates. Intracellular GSH levels in oocyte treated with 5μM of FA significantly increased (P < 0.05), and 20μM of FA revealed significant decrease (P < 0.05) in intracellular ROS levels compared with the control group. Oocytes treated with FA exhibited significantly higher cleavage rates (79.01% vs 89.19%, 92.20%, 90.89%, respectively) than the control group. Oocytes treated with 10μM showed significantly higher blastocyst formation rates (28.3% vs 40.3%, respectively) after PA than the control group. Total cell numbers in blastocyst of 10μM FA displayed significantly higher (39.4 vs 51.9, respectively) than the control group. In conclusion, these results suggested that treatment with FA during IVM improved the developmental potential of porcine embryos by increasing intracellular GSH synthesis and reducing ROS levels. Also, there was an improvement of cleavage rate, blastocyst formation and total cell numbers in blastocysts. It might be associated with Keap1-Nrf2 pathway as an antioxidant regulate pathway that plays a crucial role in determining the sensitivity of cells to oxidative damages by regulating the basal and inducible expression of enzymes which is related to detoxification and anti-oxidative effects, stress response enzymes and/or proteins and ABC transporters.